Creatine transport and its regulation in skeletal and smooth muscle - Steele, S (1995)
Despite the importance of creatine (Cr) in normal and pathological cellular metabolism, the control of intracellular Cr concentration, ([Cr]), is poorly understood. Cytosolic [Cr] is maintained at many times the passive electrochemical equilibrium value, and there is strong evidence for the existence of a Cr transporter in the cell membrane of several tissues. In this study a simple protocol for determining net creatine uptake or efflux was developed. Cr transport across the cell membrane of skeletal and smooth muscle, its modulation, and the relationship between transport and intracellular creatine were then investigated. Results from the cultured skeletal muscle cell line, G8, show that, as in other tissues, skeletal muscle Cr uptake is largely Na gradient - dependent, is electrogenic, and has a low Km for [Cr]. In this cell line several modulators were shown to increase creatine uptake; the agonists included catecholamines, IGF-I and insulin, triiodothyronine and amylin. By the use of selective agonists and antagonists the receptor subtype mediating the stimulation by catecholamines and the likely signalling pathway was identified. Similarly a tyrosine phosphorylation pathway was identified as responsible for the signal transduction of insulin and IGF-I. Evidence is provided for a role of the sodium potassium ATPase as a common mediator of the uptake signal provided by each of the positive modulators. In addition we confirm the low net creatine efflux seen in other skeletal muscle preparations. Investigation of creatine transport in the isolated perfused porcine carotid artery also identifies a sodium dependent concentrative creatine uptake and a negligible net creatine efflux. The uptake was shown to be positively modulated by isoproterenol (isoprenaline). These results are discussed in terms of the biochemical and hence functional implications for the muscle affected.